D-amino Acids Ameliorate Experimental Colitis and Cholangitis by Inhibiting Growth of Proteobacteria: Potential Therapeutic Role in Inflammatory Bowel DiseaseSummary - Satoko Umeda; Tomohisa Sujino; Kentaro Miyamoto; Yusuke Yoshimatsu; Yosuke Harada; Keita Nishiyama; Yoshimasa Aoto; Keika Adachi; Naoki Hayashi; Kimiko Amafuji; Nobuko Moritoki; Shinsuke Shibata; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
Background & Aims: D-amino acids, the chiral counterparts of protein L-amino acids, were primarily produced and utilized by microbes, including those in the human gut. However, little was known about how orally administered or microbe-derived D-amino acids affected the gut microbial community or gut disease progression. Methods: The ratio of D- to L-amino acids was analyzed in feces and blood from patients with ulcerative colitis (UC) and healthy controls. Also, composition of microbe was analyzed from patients with UC. Mice were treated with D-amino acid in dextran sulfate sodium colitis model and liver cholangitis model. Results: The ratio of D- to L-amino acids was lower in the feces of patients with UC than that of healthy controls. Supplementation of D-amino acids ameliorated UC-related experimental colitis and liver cholangitis by inhibiting growth of Proteobacteria. Addition of D-alanine, a major building block for bacterial cell wall formation, to culture medium inhibited expression of the ftsZ gene required for cell fission in the Proteobacteria Escherichia coli and Klebsiella pneumoniae, thereby inhibiting growth. Overexpression of ftsZ restored growth of E. coli even when D-alanine was present. We found that D-alanine not only inhibited invasion of pathological K. pneumoniae into the host via pore formation in intestinal epithelial cells but also inhibited growth of E. coli and generation of antibiotic-resistant strains. Conclusions: D-amino acids might have potential for use in novel therapeutic approaches targeting Proteobacteria-associated dysbiosis and antibiotic-resistant bacterial diseases by means of their effects on the intestinal microbiota community.